Energy-latency tradeoffs for data gathering in wireless sensor networks - Yang Yu; Krishnamachari, B.; Prasanna, V.K. (2004 IEEE Infocom, 2004)
We study the problem of scheduling packet transmissions for data gathering in wireless sensor networks. The focus is to explore the energy-latency tradeoffs in wireless communication using techniques such as modulation scaling. The data aggregation tree - a multiple-source single-sink communication paradigm - is employed for abstracting the packet flow. We consider a real-time scenario where the data gathering must be performed within a specified latency constraint. We present algorithms to minimize the overall energy dissipation of the sensor nodes in the aggregation tree subject to the latency constraint. For the off-line problem, we propose (a) a numerical algorithm for the optimal solution, and (h) a pseudo-polynomial time approximation algorithm based on dynamic programming. We also discuss techniques for handling interference among the sensor nodes. Simulations have been conducted for both long-range communication and short-range communication. The simulation results show that compared with the classic shutdown technique, between 20% to 90% energy savings can be achieved by our techniques, under different settings of several key system parameters. We also develop an on-line distributed protocol that relies only on the local information available at each sensor node within the aggregation tree. Simulation results show that between 15% to 90% energy conservation can be achieved by the on-line protocol. The adaptability of the protocol with respect to variations in the packet size and latency constraint is also demonstrated through several run-time scenarios.